Characterization of the complete chloroplast genome of Eriobotrya japonica in China and phylogenetic relationships - Jing Huang (Mitochondrial DNA. Part B. Resources, 2019)
Eriobotrya japonica is the most important economic fruit crop with high edible, medical as well as ornamental values in China. In this study, we presented the complete chloroplast genome of E. japonica. The chloroplast genome size is 159,107 bp, containing a large single-copy region (87,213 bp), a small single-copy region (19,268 bp), and a pair of IR regions (26,313 bp). The overall GC contents of the chloroplast genome are 36.7%. Eriobotrya japonica whole chloroplast genome contains 129 genes, including 84 protein-coding genes, 37 tRNAs, and 8 rRNAs. Phylogenetic maximum likelihood (ML) analysis based on 15 plant species chloroplast genomes indicates that E. japonica is closely related to Eriobotrya bengalensis. These complete chloroplast genomes can be subsequently used for valuable species research of Eriobotrya.